Princípio da solidariedade na bioética clínica: revisão sistematizada da literatura - Segantini, Rodrigo Leite (2017)
Solidarity, as a social value, is used in the adoption of systemic procedures for clinical decision making, as well as in the resolution of ethical dilemmas. As a bioethical principle, Solidarity was introduced by the Universal Declaration on Bioethics and Human Rights (UDBH) published by UNESCO in 2006. However, to have it scientifically applied, it is necessary to legitimate it based on a valid methodology to establish its practice. Primary objective: Identify and analyze the Principle of Solidarity applicable to the Clinical Bioethics in a way of humanizing the relationship between health professionals and the patient, and their families. Secondary objectives: A) to carry out an analysis to the texts found according to the method used in order to develop the present research; B) to establish a relationship between bioethical principles and the Principle of Solidarity. Method: A systematic review from the literature was conducted to document the Bioethical Principle of Solidarity applied to Clinical Bioethics. Data were retrieved in a broader Capes Periodicals portal (Portal Periódicos Capes) search. The primary literature search was conducted using the following search term without year restriction: Bioethical Principle of Solidarity. Data were grouped by Authors, Year and Source of Publication. After, we analyzed segmented sections that were arranged into categories of statements of semantic similarities from phenomenological reduction. We considered the principles of bioethics advocated by the Belmont Report in relation to the Bioethics Principle of Solidarity. In order to discuss the results, we used the UDBH and the pertinent literature. Results: Literature search identified 15 studies; of which ten were used in review. These studies were segmented by Authors, Year and Source of Publication. We categorized 56 significant sections relating the bioethical principles advocated by the Belmont Report to the Bioethical Principle of Solidarity. We identified that the main authors have both academic background and practice in the area of Nursing; the projection of scientific production on the subject has increased substantially since DUBDH was published in 2006, with emphasis in 2015. We further identified that publishing houses, which have promoted these studies dealing with this specific content have as their agenda the Collective Health. We also verified that the Bioethics Principle of Solidarity is more related to the Bioethical Principle of Justice or Equity and to a lesser extent to the Bioethics Principle of Autonomy. Conclusions: Solidarity in clinical is considered more as a social concept than properly as a bioethical principle. When Solidarity is understood as a scientific premise, it is more related to Principles of Justice or Equity. It is recommended that patients, their families and health professionals should understand they are inserted into a system of finite resources and limited availability. However, in clinical practice, we verified the identity of Solidarity with the Principle of Autonomy. It is implicit that allowing the patient and his/her relatives to participate in the therapy is an empathic exercise. There is a lack of research to give the Bioethical Principle of Solidarity the necessary status of scientific applicability in clinical practice.